2009
DOI: 10.1242/jcs.045625
|View full text |Cite
|
Sign up to set email alerts
|

ATF6α induces XBP1-independent expansion of the endoplasmic reticulum

Abstract: A link exists between endoplasmic reticulum (ER) biogenesis and the unfolded protein response (UPR), a complex set of signaling mechanisms triggered by increased demands on the protein folding capacity of the ER. The UPR transcriptional activator X-box binding protein 1 (XBP1) regulates the expression of proteins that function throughout the secretory pathway and is necessary for development of an expansive ER network. We previously demonstrated that overexpression of XBP1(S), the active form of XBP1 generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(212 citation statements)
references
References 50 publications
4
204
1
3
Order By: Relevance
“…Several studies have demonstrated that forced expression of cleaved ATF6α is alone sufficient to up-regulate ER chaperones (4,20,22); hence, an increase in classic UPR targets might have been expected also under our condition. It is, however, well known that ATF6α dimerizes with other transcription factors that modulate its activity (23)(24)(25).…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have demonstrated that forced expression of cleaved ATF6α is alone sufficient to up-regulate ER chaperones (4,20,22); hence, an increase in classic UPR targets might have been expected also under our condition. It is, however, well known that ATF6α dimerizes with other transcription factors that modulate its activity (23)(24)(25).…”
Section: Discussionmentioning
confidence: 80%
“…The three branches of the UPR exhibit extensive overlap in both their downstream targets and in the transcriptional networks that become activated in response to ER stress (43)(44)(45)(46). Although previous studies have linked the UPR to MIST1 activity (19,24,47), the extensive cross talk and overlap between distinct UPR branches has complicated identifying which UPR branch specifically leads to induction of MIST1.…”
Section: Resultsmentioning
confidence: 99%
“…The detrimental effects of UPR activation in the lens were probably mediated by both activation of UPR-specific transcription factors and UPR-induced global translational attenuation. The production of ATF6(N) and XBP1(S) could alter fiber cell transcriptional programs by up-regulating genes involved in ER folding and ER biogenesis in lens fiber cells that would normally undergo programmed degradation of nuclei and cytoplasmic organelles (59,62,88). On the other hand, PERK-mediated translational attenuation could interfere with lens fiber cell differentiation through lowering the synthesis of crystallins and other fiber cell-specific proteins that are needed for fiber cell differentiation.…”
Section: Discussionmentioning
confidence: 99%